Pertussis Vaccine Performance in an Epidemic Year—Oregon, 2012. (18th April 2014) - Liko, Juventila; Robison, Steve G.; Cieslak, Paul R.
Abstract : A 2012 pertussis epidemic in Oregon afforded an opportunity to measure vaccine effectiveness; it ranged from 95% (95% confidence interval [CI], 92%–97%) among children 15–47 months of age to 47% (95% CI, 19%–65%) among adolescents 13–16 years of age. In all age groups, pertussis incidence was higher among unimmunized persons.